Non-Standard Monetary Policy Measures – Magic Wand or Tiger by the Tail? - Ansgar Belke (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
This paper briefly assesses the effectiveness of the different non-standard monetary policy tools in the Euro Area. Its main focus is on the Outright Monetary Transactions (OMT) Programme which is praised by some as the ECB's 'magic wand'. Moreover, it discloses further possible unintended consequences of these measures in the current context of weak economic activity and subdued growth going forward. For this purpose, it investigates specific risks for price stability and asset price developments in the first main part of the paper. It is not a too remote issue that the Fed does have a 'tiger by the tail', as Hayek (2009) expressed it, i.e. that the bank will finally have to accept either a recession or inflation and that there is no choice in between. Furthermore, it checks on whether the OMT programme really does not impose costs onto the taxpayer. Finally, it comes up with some policy implications from differences in money and credit growth in different individual countries of the Euro Area. The second main part of the paper assesses which other tools the ECB could use in order to stimulate the economy in the Euro Area. It does so by delivering details on whether and how the effectiveness of the ECB's policies can be improved through more transparency and 'forward guidance'. – – Dieser Beitrag untersucht die Effektivität der unkonventionellen geldpolitischen Maßnahmen in der Eurozone. Der Schwerpunkt liegt dabei auf dem angekündigten Ankaufprogramm für Staatsanleihen (Outright Monetary Transactions, OMT), das von einigen als Allheilmittel angesehen wird. Darüber hinaus wird herausgearbeitet, dass die geldpolitischen Maßnahmen im Zuge der schwachen Konjunktur unerwünschte Nebeneffekte haben können. Der erste Teil dieser Arbeit beschäftigt sich dabei vor allem mit den Risiken für die Preisstabilität und der Entwicklung von Vermögenspreisen. Die amerikanische Notenbank Fed dürfte dabei in nicht allzu ferner Zukunft vor einer schwierigen Entscheidung stehen – sie muss zwischen einer Inflation oder Rezession wählen. Weiterhin fragt dieser Beitrag, ob das OMT-Programm mit Kosten für den Steuerzahler verbunden ist. Abschließend werden einige Konsequenzen für die Geldpolitik aufgezeigt, die aus den unterschiedlichen Geldmengen- und Kreditwachstumsraten in der Eurozone herrühren. Der zweite Hauptteil untersucht dann, welche alternativen Möglichkeiten der EZB zur Unterstützung der wirtschaftlichen Erholung zur Verfügung stehen. Dabei wird gezeigt, wie die Effektivität der Geldpolitik durch gesteigerte Transparenz und Orientierungshilfen verbessert werden kann.
Keywords: E52; E58; F32; 330; central bank transparency; euro area; forward guidance; non-standard monetary policies; outright monetary transactions; quantitative easing; segmentation of credit markets